Effect of moisture content on significant parameters to the surface excavation performances - Ahmad Legiman, Mariatul Kiftiah (2021)
The influence of moisture content on weathered rock arise frequent issues related to excavation works. It should be taken into consideration as unique features in tropical climate. Therefore, the need for an effective assessment on excavation works related to the moisture content is demanding. A systematic approach of field and laboratory assessments were structured with geological data collection and field trials at Sedenak, Bentong and Ulu Kinta sites. First, the field study includes geological mapping and discontinuity survey in order to characterize the weathering state, followed by thirty-six excavation trials were carried out during sunny day and after rainy days. Then, the physical properties of rock materials were determined by laboratory works including point load test, jar slake, moisture content, slake durability and petrographic analysis on forty rock samples of sandstone, shale and granite respectively. Rock masses recorded joint spacing of 0.1-2 m with maximum of four joint sets during field investigation. Sandstone and shale exhibit bedding as major type of discontinuity as compared to granitic rock which only characterized by the joints and faults. Block size shows a decreasing trend, ranges from 1-0.1 m3 with weathering degree of slightly to completely weathered. From petrographic study, it is revealed that percentage of clay in slightly weathered in sandstone, shale and granite is 2.1%, 2.7% and 0% respectively. Meanwhile, the percentage of clay in moderately weathered is found to be 36%, 45% and 10% for the similar rock types. Clay content increase in the highly weathered state with 49%, 55% and 75%. Furthermore, for completely weathering state, sandstone and shale consist of 95% of clay and granite is 90%. The incremental of clay content has been found as one of the major factors in reducing the rock material strength. It was established that reduction strength of slightly weathered sandstone and granite ranges from 5-12% and 8-10% respectively. Whereas, in moderately weathered sandstone reduced 16-20%, while in granite is 33% to 37%. The strength reduction become more significant in highly weathering state which ranges from 50-60% in sandstone and shale, while 50-57% for granite. The result shows that the block size more than 0.6 m3 could not be excavated. The case was different when it involves block size ranges from 0.15-0.5 m3 with productivity less than 15 m3/h for all type of rock for slightly weathered rock mass. In highly weathering state, block size which ranges from 0.1-0.8 m3 resulting the productivity increase between 10-45 m3/h. The case is different in completely weathered, where block size ranges 0.1-0.8 m3 does not influenced much on the productivity resulting 25-50 m3/h. It was found that increment of moisture content help to increase the productivity when the block size measured less than 0.3 m3 for all types of rocks. The productivity increased by 20-50% when excavated after heavy rain on moderately and highly weathered sandstone and shale. This study prove that moisture content could affects the performance of excavation significantly on highly weathered rock mass. The effects are minimal for completely weathered, slightly weathered and moderately weathered rock masses. The block size does not become important factor in controlling the excavation performance in the slightly and completely weathered zone.